PENGARUH CITRA DESTINASI TERHADAP NIAT BERKUNJUNG WISATAWAN KE JAKARTA - Budi (FT-TEKNIK USNI, 2019)
Destination image is important factor in tourism marketing. Destination image influences tourists’ decisions on destinations that tourists will visit. This research is quantitative research. Instruments were developed by adopting previous studies but still considering their relevance. Questionnaires are shared through the internet network. The research subjects were those who were not residents of Jakarta, and were at least 17 years old. Determination of samples using random sampling method. Validity Test, Reliability Test, Signification Test, Determinant Test, and Mediation Test were performed. Results show that according to tourists that Jakarta has varied, interesting and fun tourist attractions to visit. This positive destination image influences the intention of tourists to visit Jakarta and recommends their friends and relatives to visit Jakarta as well. The implication of this finding for tourism marketers is that cognitive destination images will influence the conative (actions) of tourists. Therefore tourism marketers should not only focus on building an induced destination image but also the organic destination image. Tourism marketers must be aware of general information circulating on public communication channels and social media regarding the tourist destinations because it will form a cognitive objective image which then affects the actions that will be taken by tourists onthe tourism destination.